the photoconductive properties of pbxs1-x films (Baghdad Science Journal, 2006)
Optical detector was manufactured Bashaddam thermal evaporation technique at room temperature under pressure rays studied characteristics of reactive Scout efficiency quantitative ratio of the signal and the ability equivalent to noise